An overview on the use of geosynthetics in pavement structures - Mounes, S.M.; Karim, M.R.; Mahrez, A.; Khodaii, A. (2011)
Pavement structures commonly fall into two main categories, namely, flexible and rigid pavements. Such structures just as other structures are susceptible to different types of distresses. In order to minimize the deterioration of pavements, geosynthetic reinforcement is one of the techniques adopted to improve their performance. As a result, employment of different geosynthetics to pavement structures is reported by various researchers. This paper aims to present and discuss the findings from some of the studies on utilizing geosynthetics in flexible pavements. Furthermore, three most common usages of geosynthetics, so called, fluid barrier, strain absorbing, and reinforcement agent in pavement structures are investigated in this paper. Â© 2011 Academic Journals.